Update breast cancer 2018 (Part 3): genomics, individualized medicine and immune therapies - in the middle of a new era : prevention and treatment strategies for early breast cancer = Update Mammakarzinom 2018 (Teil 3) : Genomforschung, individualisierte Medizin und Immuntherapien - mitten in einer neuen Ära: Prävention und Therapie des frühen Mammakarzinoms - Wöckel, Achim; Lux, Michael P.; Janni, Wolfgang; Hartkopf, Andreas D.; Nabieva, Naiba; Taran, Florin-Andrei; Overkamp, Friedrich; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; Lüftner, Diana; Müller, Volkmar; et al. (Geburtshilfe und Frauenheilkunde, 2018)
In primary early breast cancer, the aim of treatment planning is to obtain an increasingly better understanding of the disease. The identification of patients with an excellent prognosis could help this group avoid unnecessary treatments. Furthermore, the planning of treatment is becoming increasingly patient-focussed. There is a growing understanding of those patients who benefit particularly from chemotherapy, as well as of those who could benefit from immunotherapy. Studies conducted on immunotherapies will be published shortly. Smaller individual studies offer an initial insight into the efficacy of checkpoint inhibitors (anti-PD1/PDL1 therapies). Not least, one of the largest breast cancer studies of all times has recently come to an end. The use of a multigene test has shown that it is sufficient to identify patients with such a good prognosis that chemotherapy is unnecessary. This review article is intended to summarise the current studies and give an outlook on current developments.
Gesehen am 23.04.2020